Mental health care technologies for treating crack users - Cintia Nasi; Gustavo Costa de Oliveira; Annie Jeanninne Bisso Lacchini; Jacó Fernando Schneider; Leandro Barbosa de Pinho
The aim of this study was to identify mental health care technologies for treating crack users in a Psychosocial Care Center for Alcohol and other Drugs (CAPsad, as per its acronym in Portuguese). A qualitative, evaluative case study was developed in a CAPSad, using fourth generation evaluation. Data collection occurred from January to March 2013 by means of semi-structured interviews applied to 36 subjects, these being health care professionals, patients, patients' relatives and managers. Data analysis identified the category strategies in mental health work. Results showed that recovery programs should provide spaces for dialogue, aiming to clarify the process of psychiatric internment to the user and family, and involve these in the therapy, implementing educational practices and ongoing consideration of mental health activities. In conclusion, it is important to discuss the technologies used in everyday care services, in light of the complexity of crack use.